Enzymatically degradable nanoparticles of dextran esters as potential drug delivery systems - Kulthida Kaewprapan (2018)
Dextran decanoate esters with degrees of substitution (average molar ratio of ester functions to glucose repeat units) between 20 and 150% were used to form nanoparticles via nanoprecipitation technique. Particle size and colloidal stability of nanoparticles were found to depend on dextran concentration and degree of substitution. The colloidal stability of nanoparticle suspensions in sodium chloride solutions was improved by using a water-soluble dextran derivative as stabilizer. Enzymatic hydrolysis of ester bonds by porcine pancreatic lipase was demonstrated for highly modified dextran derivatives (up to DS = 150%). Complete degradation of low modified dextrans (DS up to 25%) by dextranase occurred within 7 days. Finally, encapsulation of lidocaine (as a model drug) into nanoparticles obtained with dextran esters (DS ranging between 21 and 150%) was investigated. © 2012 Elsevier Ltd. All rights reserved.